A Caenorhabditis elegans Host Model Correlates with Invasive Disease Caused by Staphylococcus aureus Recovered during an Outbreak in Neonatal Intensive Care. Issue 3 (2012) - Wu, Kaiyu; Simor, Andrew E; Vearncombe, Mary; McClure, Jo-Ann; Zhang, Kunyan
Abstract : BACKGROUND: Caenorhabditis elegans has previously been used as a host model to determine the virulence of clinical methicillin-resistant Staphylococcus aureus isolates. In the present study, methicillin-susceptible S aureus (MSSA) strains associated with an outbreak in a neonatal intensive care unit (NICU) were investigated using the C elegans model. METHODS: Two distinct outbreak clones, MSSA type-C and MSSA type-G, were identified by pulsed-field gel electrophoresis in a MSSA outbreak during a seven-month period in the NICU of the Sunnybrook Health Sciences Centre (Toronto, Ontario). MSSA type-C was associated with severe infection, while type-G was associated with less invasive disease. Four representative type-C isolates, three type-G and three infant-colonized isolates unrelated to the outbreak, were sent to Calgary (Alberta), for the double-blinded virulence tests in the C elegans host model and for further molecular characterization. RESULTS: The invasive outbreak strains (type-C) demonstrated highly nematocidal activity, the noninvasive outbreak strains (type-G) an intermediate virulence, and the outbreak-unrelated colonization isolates demonstrated avirulence or low virulence in the C elegans model, with mean killing rates of 93.0%, 61.0% and 14.4% by day 9, respectively, for these three group strains. Different group MSSA strains had their own unique genetic profiles and virulence gene profiles, but all isolates within the same group (type-C or type-G) shared identical genetic characteristics and virulence gene patterns. CONCLUSIONS: The present blinded evaluation demonstrated that the nematocidal activities of MSSA strains correlated well with the clinical manifestation in an MSSA outbreak in the NICU, supporting C elegans as a robust host model to study the pathogenesis of S aureus .